2016
DOI: 10.1016/j.earlhumdev.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy tube placement in infants with congenital diaphragmatic hernia: Frequency, predictors, and growth outcomes

Abstract: Background Gastrostomy tube (G-tube) placement is a common intervention for newborns with severe feeding difficulties. Infants with congenital diaphragmatic hernia (CDH) are at high risk for feeding problems. Prevalence of G-tube placement and consequent nutritional outcomes of infants with CDH and G-tubes has not been described. Aims Determine factors associated with G-tube placement and growth in infants with congenital diaphragmatic hernia. Study design Retrospective cohort study of infants with CDH to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…G‐tube placement was not associated with improved short‐term weight gain in our cohort of hospitalized premature infants. This finding is consistent with previous findings in infants with congenital diaphragmatic hernia, in which G‐tubes were not associated with improved growth . Nevertheless, in populations with special medical conditions that predispose to poor growth and nutrition such as ultrashort gut, Pierre Robin syndrome, and cystic fibrosis, G‐tube placement has been associated with improved weight gain …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…G‐tube placement was not associated with improved short‐term weight gain in our cohort of hospitalized premature infants. This finding is consistent with previous findings in infants with congenital diaphragmatic hernia, in which G‐tubes were not associated with improved growth . Nevertheless, in populations with special medical conditions that predispose to poor growth and nutrition such as ultrashort gut, Pierre Robin syndrome, and cystic fibrosis, G‐tube placement has been associated with improved weight gain …”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous findings in infants with congenital diaphragmatic hernia, in which G-tubes were not associated with improved growth. 9 Nevertheless, in populations with special medical conditions that predispose to poor growth and nutrition such as ultrashort gut, Pierre Robin syndrome, and cystic fibrosis, Gtube placement has been associated with improved weight gain. [10][11][12] Children with neurodevelopmental disabilities have been the most studied population, with apparent long-term benefits of growth and quality of life associated with G-tube placement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the safety profile of these medications in this cohort is uncertain. One study noted an association between increased PPI use and FT placement; however, neither intervention was associated with improved growth 23 . Understanding the reasons for poor growth in infants with CDH is helpful for clinicians caring for these complex patients, and the summary of current literature suggests that markers of disease severity are most tightly correlated with limited growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gastrostomy was required in 39 (32%) patients and fundoplication in 23 (19%). In a small retrospective cohort study of infants with CDH treated at Duke University (Durham, NC), gastrostomy tubes were placed in 29% of survivors (ECLS associated with gastrostomy tube placement [OR 11.26; 95% confidence interval, 1.92–65.89; P = 0.01]), however infants without gastrostomy tubes had a growth velocity 6.5 grams/day higher than infants with gastrostomy …”
Section: Long‐term Nutrition Considerationsmentioning
confidence: 99%
“…In a small retrospective cohort study of infants with CDH treated at Duke University (Durham, NC), gastrostomy tubes were placed in 29% of survivors (ECLS associated with gastrostomy tube placement [OR 11.26; 95% confidence interval, 1.92-65.89; P = 0.01]), however infants without gastrostomy tubes had a growth velocity 6.5 grams/day higher than infants with gastrostomy. 31 In the first study examining if poor growth persists during childhood in CDH survivors, Leeuwen et al demonstrated that poor linear growth persists at 12 years of age, particularly in those survivors who received ECLS. 32 More optimal outcomes following ECLS for CDH survivors, including breastfeeding success, are documented.…”
Section: Long-term Nutrition Considerationsmentioning
confidence: 99%